What does the educational investigator mean when talks about teaching work? - Cervantes Holguín, Evangelina (Atenas, 2016)
This paper explores some approaches to the field and definition of teaching work, with emphasis on the specific problems and the dimensions of analysis that contribute to the construction of a new rhetoric about the increasing complexity of the teaching performance. Through the reflection of various arguments that converge to a definition of teaching work, we can identify six central themes studied for the educational researchers: health, processes and conditions of teaching work, subjectivity and identity, gender, education policy with emphasis on teacher training and evaluation, and trade unionism.